Framing John Delorean [videorecording (DVD)] - Argott, Don; Joyce, Sheena M.; Baldwin, Alec, 1958-; Charles, Josh, 1971-; Winters, Dean, 1964- (Shout! Factory, 2019)
Money, power, politics, drugs, scandal, and fast cars: the incredible story of John DeLorean is the stuff of a Hollywood screenwriter's dreams. But who was the real John DeLorean? To some, he was a renegade visionary who revolutionized the automobile industry. To others, he was the ultimate con man. Interweaving archival footage with dramatic vignettes, look at a man who gambled everything in pursuit of the American Dream.